Pengembangan Buku Ajar Berbasis Media Gambar Pada Tema 7 Subtema 1 Di Kelas 1 Sekolah Dasar - Anisa Andriani; Andi Suhandi (Jurnal Tonggak Pendidikan Dasar : Jurnal Kajian Teori dan Hasil Pendidikan Dasar, 2022)
This research aims to describe how to develop textbooks, describe the level of validity of textbooks, describe the practicality of image media-based textbooks on theme 7 subtheme 1 in grade 1 elementary school about living objects and non-living objects around me. In this research, the development design model used is the ADDIE development model where there are 5 main phases or stages, including: analysis, design, development, implementation, and evaluation. Data collection was obtained by conducting interviews with related parties regarding the constraints of teachers and students regarding image media-based textbooks in theme 7 subtheme 1 in grade 1 of elementary school, the second data collection used a questionnaire. The questionnaire is used to collect data regarding the accuracy of textbook components, accuracy of learning design, accuracy of textbook content, validity and practicality of using textbooks. The next data collection is documentation. Documentation is taken in the form of photos of all activities or activities during the research. The final data collection is by means of tests. Tests are used to collect data regarding post-test results which can show the effectiveness of student learning after using image-based textbooks.